Rendering Gaza Visible: The Visual Economy of the Nakba in Palestinian Films of the Oslo Period - Rastegar, Kamran (Tufts University. Tisch Library., 2023)
Contributors to Gaza on Screen, including scholars and Gazan filmmakers, explore the practice, production, and impact of film and videos from and about the Gaza Strip; Keywords: film, Palestine, media, resistance, news, solidarity, humanitarianism.; Funding for open access publishing provided by the Tufts Faculty Research Awards Committee (FRAC).